A theory of dialectical transnational historical materialism for China's state capitalism and the China–US rivalry. Issue 7 (28th June 2022) - Chen, David
Abstract: A new cold war seems to be looming between China and the United States. The escalating China–US rivalry calls for a more dialectical theory of international political economy that captures conflict and disintegration as an integral part of capitalist globalisation. Kees van der Pijl's and William Carroll's critical realist approach towards the study of transnational corporations (TNCs) and transnational capitalist class (TCC) formation has incorporated the classical theory of uneven capitalist development and inter-imperialist rivalry into the scholarship of transnational historical materialism, which I argue is apt for explaining the China–US conflict: One is positioned as a Hobbesian contender and the other as the Lockean hegemon. To provide empirical grounding for my argument, I conduct a corporate network study to examine the interlocking directorates of 40 Chinese TNCs. In concordance with Carroll and colleagues' studies, I find that the globalisation of Chinese TNCs and Chinese corporate elite has been modest and has not undermined or replaced the national base, nor does it signify a homogeneous TCC formation. My findings have also revealed an inextricable relationship between the Chinese TNCs and China's party-state, or a Hobbesian character of state-organised capitalism.